Evaluation of Some Approved Computer Studies Textbooks In Use In Junior Secondary Schools In Ebonyi State Of Nigeria - Umoke, Chukwudum; Nwafor, C. E. (Advances in Social Sciences Research Journal, 2015)
This study was designed to evaluate the content adequacy and readability of computer studies textbooks in use in junior secondary schools in Ebonyi state of Nigeria. Eight research questions and two hypotheses guided the study. The sample of the study consisted of three (3) approved computer studies textbooks, 21 junior secondary schools randomly selected from the 3 education zones of Ebonyi State, and 56 computer studies teachers in Ebonyi State. Three (3) instruments were used for data collection: (1) computer studies Textbooks Readability Test (CSTRT) (II) 8-point model by Emerole (2008), an update of quantitative approach to the content evaluation of science textbooks (QACEST) by Nworgu (2001) (III) Teachers’ Perception Rating Scale (TPRS). The 8-point model of QACEST was used to answer research questions 1,2,3,4,5 and 7, research question 6 was answered by using cloze model of readability measurement. The two hypotheses were tested at 0.05 level of significance using chi-square test of goodness of fit. The results of the findings showed that the some approved computer studies textbooks, have adequate contents and learning activities. It also revealed that some of the textbooks has no chapter summaries, the illustrations, chapter summaries, study questions, in some of the textbooks were inadequate. The findings also indicated that the textbooks were culturally, ethnically and gender biased. Based on the findings, conclusions were drawn and was recommended that computer textbooks should be revised periodically to enrich the contents and readability of the textbooks and that a committee of specialists in computer studies should be appointed to selected and possibly approve computer studies textbooks when the need arises, among others.